PENGEMBANGAN SISTEM INFORMASI SIMPAN PINJAM DI KOPERASI KELUARGA UNIVERSITAS GADJAH MADA (KOKELGAM) - , TSANIA HANINTISYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The unit is part of the savings and loans played a major role in a cooperative to help the passage of a cooperative activity. The unit has the task to the savings and loan savings and loan management set members, which includes the recording of the new members, payment of deposits and lending cooperatives and reporting. Savings and loans co-operative information system is designed as a tool for operational savings and loans cooperative unit that is capable of handling data processing members, savings and loans and reporting of data. Savings and loans co-operative information system is built using a web-based framework and the CodeIgniter PHP programming language and MySQL for its database management. The results of the Savings and Loans Cooperative Information Systems is a member statements, reports and member savings and loan cooperative financial statements based on period of time.